2008
DOI: 10.1002/jsfa.3363
|View full text |Cite
|
Sign up to set email alerts
|

Oil recovery and lecithin production using water degumming sludge of crude soybean oils

Abstract: BACKGROUND: Wet gums produced during aqueous degumming of crude soybean oils are currently processed to produce lecithin or added to meals to increase their nutritive value for animal feed. Oils occluded in these gums are generally not recovered or processed. In this work, three methods to recover occluded oil and obtain lecithin from wet gums were assayed: direct extraction of oil with cold acetone (Method I), extraction after water elimination under vacuum (Method II) and by solvent partition with hexane/eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Phospholipids (PL) present in the total lipidic amount (1-3 g) obtained by Soxhlet extraction were separated and quantified by dispersion in cold acetone (90 ml), which is assumed to only dissolve neutral lipids [19,20]. In this work, the fraction of lipids which is insoluble in acetone is assumed to be the PL fraction.…”
Section: Soxhlet Extraction and Characterization Of Extracted Lipidsmentioning
confidence: 99%
“…Phospholipids (PL) present in the total lipidic amount (1-3 g) obtained by Soxhlet extraction were separated and quantified by dispersion in cold acetone (90 ml), which is assumed to only dissolve neutral lipids [19,20]. In this work, the fraction of lipids which is insoluble in acetone is assumed to be the PL fraction.…”
Section: Soxhlet Extraction and Characterization Of Extracted Lipidsmentioning
confidence: 99%
“…[95] Liliana et al wrote that phospholipids (gums) produced during water degumming of crude soybean oils are currently processed to produce lecithin or added to meal to increase their nutritive value for animal feed. [96] Spring 2005 reported that Lecithin is mainly used in sauces and salad dressings as an emulsifier, in chocolate, as anti-spattering agents in margarine, as pan release agents in bakery and confectionery, as dough improvers and staling retardants in bread, and as wetting agents in instant food powders. They also have some antioxidant properties.…”
Section: Application Of Degummed Vegetable Oil As a Biofuelmentioning
confidence: 99%
“…Lecithin is a commercial term designating a complex mixture of polar lipids (phospholipids and glycolipids), triacylglycerols, and smaller amounts of other substances . It is a byproduct of the degumming process of crude vegetable oils and is produced by further purification and fractionation of the gums . Soybean was previously the primary oilseed source of lecithin because of availability of the oil and functionality of its lecithin .…”
Section: Introductionmentioning
confidence: 99%